Implementasi Islamic Math Character: Paradigma Baru dalam Pembelajaran Matematika - Karim, Muhammad Busyro; Asyhar, Ahmad Hanif (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2016)
This research aimed to describe student learning outcomes trough implementation of Islamic Math Character and explain whether of Islamic Math Character can improve student learning outcomes in subject Calculus I. This research is an action research which uses a classroom action research with spiral model. Each cycle consist of planning, action, observation, and reflection. The research subject were Calculus I students of mathematics education department. The research results of student learning the material functions through the application of mathematics with Islamic Math Character proved a significant increase of the value of the average of student mastery learning at pre-action only amounted to 63.78 by 31,11%. At the first cycle, the average value of student mastery learning increased to 70.33 by 57.78%. At the second cycle, the average value of student mastery learning becomes 75.44 by 100%.